2005
DOI: 10.1017/s1352465804001791
|View full text |Cite
|
Sign up to set email alerts
|

Brief Cognitive Behavioural Therapy for Depression Associated with Parkinson's Disease: a Single Case Series

Abstract: The feasibility of a brief home based cognitive behavioural intervention for depression associated with Parkinson's Disease (PD) was evaluated. Five depressed patients with PD participated. Their ages ranged from 54 to 82 and they all attended a movement disorder clinic. Outcome was assessed using mood and quality of life inventories (Beck Depression Inventory; Geriatric Depression Scale; Parkinson's Disease Quality of Life Questionnaire). Four individuals demonstrated a clinically reliable reduction of sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…These results were also comparable to the few additional in-person CBT pilot studies for dPD conducted to date 46,48,49,50,51 and are consistent with the literature on phone-based psychotherapy for depression in other patient groups 21 . Importantly, this study provides preliminary evidence that the beneficial effects of telephone psychotherapy observed in other chronic medical conditions are not attenuated by the neuropsychiatric complexity that is characteristic of the PD population.…”
Section: Discussionsupporting
confidence: 88%
“…These results were also comparable to the few additional in-person CBT pilot studies for dPD conducted to date 46,48,49,50,51 and are consistent with the literature on phone-based psychotherapy for depression in other patient groups 21 . Importantly, this study provides preliminary evidence that the beneficial effects of telephone psychotherapy observed in other chronic medical conditions are not attenuated by the neuropsychiatric complexity that is characteristic of the PD population.…”
Section: Discussionsupporting
confidence: 88%
“…Two studies using single‐case experimental design methodology reported efficacy of CBT for anxiety and depression in PD. Cole and Vaughan reported on 5 individuals with PD and depression who received 7 sessions of CBT. Four of the 5 patients were considered recovered on depression on the GDS at 1‐month follow‐up.…”
Section: Efficacy Of Cbt For Depression and Anxiety In Pdmentioning
confidence: 99%
“…As participants were not randomly assigned to treatment condition, endorsed very mild depressive symptoms at baseline, and had comparison groups that were unequal in size, only very limited conclusions may be drawn from this study [51]. An uncontrolled 15-patient pilot study [52] and several case reports have also documented the feasibility of CBT for dPD [53,54]. Moreover, an eightsession group educational program for PD patients and their caregivers that introduced many of the skills covered in CBT, such as self-monitoring, stress management, dealing with negative thoughts, and appropriate use of social supports, was pilot tested with 36 participants [55].…”
Section: Depression and Parkinson's Diseasementioning
confidence: 99%